Sex-based differences in neurocognitive functioning in HIV-infected young adults. (14th January 2018) - Burlacu, Ruxandra; Umlauf, Anya; Luca, Anca; Gianella, Sara; Radoi, Roxana; Ruta, Simona M.; Marcotte, Thomas D.; Ene, Luminita; Achim, Cristian L.
Abstract : Introduction: Sex differences in cognition of HIV positive (HIV + ) patients are controversial. We aimed to investigate the relationship between cognition, HIV status, and sex, in a highly homogenous cohort of young Romanians parenterally infected during early childhood. Methods: In total, 250 HIV + participants were compared with age-matched HIV negative (HIV − ) controls ( n = 72) in a cross-sectional study. After standardized neurocognitive, psychological testing and medical evaluation, linear regression was used to assess the effect of sex and HIV on neurocognitive outcomes. Results: Study participants were on average 23 years old with balanced sex distribution (% women = 52% vs. 43%). HIV − were more educated (12.7 vs. 11.6 years, P = 0.002). HIV + status was associated with a lower global performance (β = −0.22, P < 0.001), after controlling for age and education. HIV + women had better previous and current HIV-associated markers. The effect of HIV on global cognition did not differ between sexes in most cognitive domains (β = 0.07, P = 0.14). An interaction between sex, HIV status, and cognitive functioning was found in the psychomotor domain. HIV + women had worse motor skills than HIV − women (β = −0.32, P < 0.001) suggesting a specific effect of HIV on motor functioning in women only. Moreover, current CD4 + less than 200 cells/μl ( P = 0.013) and longer time lived with CD4 + less than 200 cells/μl ( P = 0.023) were negatively correlated with the motor scaled score in women (β = −0.22, P = 0.034). Conclusion: Despite less advanced disease in women, long-term HIV infection has an equally detrimental effect on cognitive performances of both sexes, in all cognitive domains, except the psychomotor domain where women are preferentially affected.